Sağlık çalışanlarının endüstri̇ 4.0 uygulamalarına yöneli̇k algılarının teknoloji̇ kabul modeli̇ ile incelenmesi̇ - Teker, Emir (My University, 2023)
Bu çalışma, teknoloji kabul modelini kullanarak sağlık çalışanları tarafından teknoloji kabulünün incelenmesini amaçlamaktadır. Endüstri 4.0 ilerlemelerini desteklemek için sağlık çalışanlarının sağlık sektöründeki teknolojik gelişmelere ilişkin algılarını, özellikle COVID-19 salgını ışığında anlamayı amaçlamaktadır. Veriler, özel bir sağlık grubunun çeşitli şubelerinden ve İstanbul'daki kamu eğitim- araştırma hastanelerinden çevrimiçi anket yoluyla toplanmıştır. Anket, demografik bilgileri, COVID-19 kapsamını, algılanan kullanım kolaylığını ve algılanan faydayı kapsayan bölümlerden oluşmaktadır. Teknoloji kabul modeli çerçevesinde elde edilen verilen üzerinde SPSS kullanılarak faktör analizi, boyutlar arası ilişkiyi anlamak için korelasyon analizi, demografik değişkenler ve boyutlar arasındaki karşılaştırmalar t-testi ve ANOVA analizleri kullanılarak incelenmiştir. Çalışma sonucunda COVID-19 sürecine ilişkin Algılanan Fayda, Algılanan Kullanım Kolaylığı ve COVID-19 Bilgi Teknolojileri Gelişim boyutları arasında pozitif bir ilişki olduğunu ortaya konuldu. Özellikle Algılanan Kullanım Kolaylığı ile COVID-19 Süreci Bilgi Teknolojileri Gelişimi boyutu arasında en güçlü ilişki gözlendi. Tüm boyutlar ve dışsal değişkenler incelendiğinde cinsiyet, yaş, deneyim, eğitim düzeyi ve kurum türü grupları arasında anlamlı farklılıklar tespit edildi.

This study aims to examine the technology acceptance by health professionals using the technology acceptance model. It aims to understand the perceptions of healthcare professionals regarding technological developments in the healthcare sector, especially in the light of the COVID-19 pandemic, in order to support Industry 4.0 advances. The data were collected through an online survey from various branches of a private health group and public educational and research hospitals in Istanbul. The survey consists of sections covering demographic information, COVID-19 coverage, perceived ease of use and perceived benefit. Factor analysis using SPSS on the data obtained within the framework of the technology acceptance model, correlation analysis to Dec Decently understand the relationship between dimensions, comparisons between demographic variables and dimensions were examined using t-test and ANOVA analyses. As a result of the study, it was revealed that there is a positive relationship between the Perceived Benefit, Perceived Ease of Use and COVID-19 Information Technology Development dimensions related to the COVID-19 process. Dec. In particular, the strongest relationship was observed between the Perceived Ease of Use and the COVID-19 Process Information Technology Development dimension.Dec. When all dimensions and external variables were examined, significant differences were found between gender, age, experience, educational Deciency and institution type groups.
A research on health professionals' perceptions towards industry 4.0 applications with technology acceptance model
Keywords: COVID-19; COVID-19 Industry 4.0; Endüstri 4.0; Endüstriler; Health 4.0; Industries; Medical personnel; Sağlık 4.0; Sağlık personeli; Technological innovations; Technology Acceptance Model; Teknoloji Kabul Modeli; Teknolojik yenilikler